Description of the female of Pintomyia (Pifanomyia) deorsa (Diptera, Psychodidae, Phlebotominae) - Galati, Eunice A. B. (2018)
Pintomyia (Pifanomyia) deorsa (Pérez, Ogusuku, Monje & Young, 1991) was described on the basis of a single male; the female is being described here from specimens collected in Ollantaytambo, Cusco, Peru. Diagnoses for the Pintomyia genus, Pifanomyia subgenus, Verrucarum series and both sexes of Pi. deorsa are presented, as well as an identification key to distinguish the females of the Verrucarum series.